Selected aspects of end-of-life care in the Intensive Therapy Unit (Journal of Medical Science, 2015)
End-of-life (EOL) care represents a significant component of palliative/hospice care. It is applied in terminal hours, days or weeks of life, which require a very scrupulous, professional protection and paliative treatment, targeted at alleviation of sufferings. Mortality in wards of anaesthesiology and intense therapy (ICU) reaches 17%-24% and frequently, despite application of modern therapeutic methods, the patient dies. This paper aims at drawing readers’ attention to selected aspects of care given to patients and their families in the end-of-life in ICU. Dying represents a very difficult process not only for the patient and his/her family but also for the staff taking care over the patient. It represents a dynamic process and, therefore, the management should be modified depending on altering condition of a patient and his/her relatives; it is linked to adaptation of care and symptomatic treatment and to meeting half-way anxieties of patient’s relatives. The patient should be viewed in his/her entire set of biological, psychic, spiritual and social needs and it should be born in mind that securing an appropriate comfort of terminal moments in life is occasionally more important than a heroic battle for every minute of life. In the terminal period of life quality of life depends on an appropriate communication, acceptance that the patient and his/her family keep the key for undertaking decisions, for a continuous care, emotional support, for assurance of an appropriate care, correct symptomatic treatment, spiritual, emotional and organizational support.